Shallow Literacy, Timid Teaching, and Cultural Impotence - David L. Wallace (Journal of the Assembly for Expanded Perspectives on Learning, 2004)
Any attempt to move to a deeper notion of literacy in our theory and pedagogy must—among other things—involve us facing our own self interest and expecting disruption in our own classrooms, departments, and universities.